Cam Dynamic Synthesis - T. Petrescu, Florian Ion; Petrescu, Relly Victoria V. (Al-Khwarizmi Engineering Journal, 2017)
The paper presents an original method to make the geometric synthesis of the rotary cam and translated tappet with roll. Classical method uses to the geometric synthesis and the reduced tappet velocity, and in this mode the geometric classic method become a geometric and kinematic synthesis method. The new geometric synthesis method uses just the geometric parameters (without velocities), but one utilizes and a condition to realize at the tapped the velocities predicted by the tapped movement laws imposed by the cam profile. Then, it makes the dynamic analyze for the imposed cam profile, and one modify the cam profile geometric parameters to determine a good dynamic response (functionality). In this mode it realizes the dynamic synthesis of the cam, and we obtain a normal functionality.